School Quality Assurance Feedback: Its Role in Promoting the Teaching Process in Public Secondary Schools in Temeke Municipality, Tanzania - Mutemi, D. Theresa; Prospery M. Mwila (Action Research Journal Indonesia (ARJI), 2025)
This study was conducted in Temeke District, Dar es Salaam, Tanzania, to examine the role of school quality assurance feedback in improving the teaching process in public secondary schools. The research was driven by concerns regarding the effectiveness of school quality assurance visits conducted by School Quality Assurance Officers (SQAOs), as student learning outcomes in the district continue to underperform despite ongoing assessments. Guided by Scientific Management Theory and the Context, Input, Process, and Product (CIPP) Evaluation Model, the study employed a qualitative case study design. A purposive sample of twenty-seven (27) participants was selected, with data collected through in-depth, face-to-face interviews and documentary analysis. Thematic analysis was used to organize, interpret, and present the data through direct quotations and narrative descriptions. The findings revealed that school quality assurance assessment is a crucial component of the education system, with feedback reports playing a significant role in enhancing teaching practices. However, the study identified key operational challenges. These included an insufficient number of officers per school visit, inadequate time spent during visits, and delays in the preparation and dissemination of feedback reports due to heavy workloads. While schools generally implement feedback recommendations, district-level responses remain limited. The study recommends increasing the number of officers and extending the duration of school visits, promoting the adoption of School Self-Evaluation (SSE) systems, and enhancing staffing and operational efficiency within the School Quality Assurance Directorate. These measures are essential for strengthening the quality assurance framework and improving educational outcomes in Temeke District’s public secondary schools.